Knowledge Management Performance Award (KMPA) For Universities & Institutes Of Higher Education. - Nejati, Mostafa; Md Shahbudin, Amirul Shah; Amran, Azlan; Nejati, Mehran (2009)
As one of the main sources of competitive advantage, knowledge has become an increasingly important resource in enabling organizattons to survive the complexities of the market and business world. It has also acted as a means to create extra opportunitiesfor the organizations. Effective use of knowledge has contributed to the development of organizational capabilities and brought about sustainable competitive advantages to the firms: Therefore, nowadays and with the emergence of knowledge era. organizations tend more to find ways to effectively manage their knowledge assets and knowledge management (KM) processes. Universities and institutes of higher education are especially important in this regard, because they can be considered as heralds of knawledge creation and bases of knowledge dissemination.